Role of βPix in the Kidney - Staruschenko, Alexander; Sorokin, Andrey (Frontiers in Physiology, 2012)
Small GTPases function as molecular switches in cell signaling, alternating between an inactive, GDP-bound state, and active GTP-bound state. βPix is one of guanine nucleotide exchange factors (GEFs) that catalyze the exchange of bound GDP for ambient GTP. The central goal of this review article is to summarize recent findings on βPix and the role it plays in kidney pathology and physiology. Recent studies shed new light on several key questions concerning the signaling mechanisms mediated by βPix. This manuscript provides a review of the various mechanisms whereby βPix has been shown to function within the kidney through a wide range of actions. Both canonical GEF activity and non-canonical signaling pathways mediated by βPix are discussed. Distribution patterns of βPix in the kidney will be also covered. Much has yet to be discerned, but it is clear that βPix plays a significant role in the kidney.